2013
DOI: 10.1039/c3em00168g
|View full text |Cite
|
Sign up to set email alerts
|

Combining multivariate statistics and analysis of variance to redesign a water quality monitoring network

Abstract: The objective of this paper was to demonstrate how multivariate statistics combined with the analysis of variance could support decision-making during the process of redesigning a water quality monitoring network with highly heterogeneous datasets in terms of time and space. Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HCA) were selected to optimise the selection of water quality parameters to be monitored as well as the number and location of monitoring stations. Sampling frequency wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
0
10
0
4
Order By: Relevance
“…It is common to observe a relationship between the first [45,47,48] or second [49] principal components and organic matter variables (COD and BOD) and an inverse relationship with DO in PCA analyses of basins contaminated by urban processes. However, as Gigues et al [50] and Pejman et al [51] demonstrate, different behaviors are found in rural basins. Fats and oils (OG), dissolved oxygen (DO), and pH exhibited low variability throughout the river and did not significantly contribute to either of the first two principal components.…”
Section: Resultsmentioning
confidence: 98%
“…It is common to observe a relationship between the first [45,47,48] or second [49] principal components and organic matter variables (COD and BOD) and an inverse relationship with DO in PCA analyses of basins contaminated by urban processes. However, as Gigues et al [50] and Pejman et al [51] demonstrate, different behaviors are found in rural basins. Fats and oils (OG), dissolved oxygen (DO), and pH exhibited low variability throughout the river and did not significantly contribute to either of the first two principal components.…”
Section: Resultsmentioning
confidence: 98%
“…Likewise, Mohamed et al (2015) used these methods to optimize a water quality monitoring network in the basin of the Klang River and were very satisfied with the obtained results [30]. Guigues et al (2013) integrated ANOVA and multivariate statistical methods to redesign a water quality monitoring network [31]. They concluded that this technique was very applicable in understanding the complex nature of water quality issues and determining the priorities to improve water quality.…”
Section: Statistical Test Results By Monthmentioning
confidence: 99%
“…Regarding the water management, whose influence during the period of investigation appeared to be rather low (except for the pumping stations at gauge Q025), a clear change (e.g., the activation of a further pumping station) would cause the optimal network to be reevaluated [cf. Guigues et al ., ]. However, to define the point in time when the change becomes severe would be hard to predict.…”
Section: Discussionmentioning
confidence: 99%